Seismic analysis of Souk Tlata dam behaviour using finite element simulation - Samia Louadj; Lila Smail (Journal of Building Materials and Structures)
In this study, earthquake resistance of Souk Tlata earth dam was examined. It corresponds to a preliminary investigation of the behaviour of the dam under earthquake loading with a dominant frequency close to the fundamental frequency of the dam. The dam was modeled with plane-strain finite elements using Plaxis-2D program. The behaviour of both the fill and core of the dam is described using the simple non associated Mohr-Coulomb criterion. The development of the safety factors as a function of the displacement of the dam crest dam reveals that the static stability of the dam under conditions of drawdown is not assured. Dynamic analyses are conducted under a real earthquake motion, which corresponds to the main shock of May 21, 2003 in Algeria. The results show that the seismic loading, with peak acceleration exceeding 0.10g, induces significant settlement at the crest of the dam and substantial displacement in the upper part of the rip-rap in the upstream side.